LATE ORIGINATING VOCAL POLYPHONY IN LATVIAN TRADITIONAL MUSIC. DOCUMENTATION AND RESEARCH (Mūzikas akadēmijas raksti, 2024)
Latvian traditional music has two main forms of polyphony – ancient and late origin polyphony. The latter developed under the influence of functional harmony. Vocal polyphony was mentioned and more or less described by a number of Latvian folk music researchers, in works by Andrejs Jurjāns, Jēkabs Graubiņš, Jānis Mediņš, Emilis Melngailis, Maksis Goldins, Jēkabs Vītoliņš, Andrejs Krūmiņš and others. Nevertheless, there are only a few broader scientific research cases in which the authors focus directly on the problem of vocal polyphony.